Development of a mobile APP to promote physical activity in individuals with knee osteoarthritis: the “Move for Knee”™ study protocol - Liguori, Sara; Andreozzi, Viviana; Moretti, Antimo; Angari, Roberta; Paoletta, Marco; Iolascon, Giovanni; Gimigliano, Francesca (Frontiers in Rehabilitation Sciences, 2025)
In modern society, physical activity is essential for maintaining both physical and mental health, particularly as technological advancements have contributed to a sedentary lifestyle. The World Health Organization recommends a minimum of 150 minutes of moderate exercise weekly for adults; however, many individuals, especially those with knee osteoarthritis (KOA), do not meet these guidelines. KOA, the most common form of arthritis, affects millions globally and leads to significant disability, pain, and reduced quality of life. The condition is exacerbated by sedentary behavior and high body mass index (BMI). Educational interventions promoting lifestyle changes, including increased physical activity, have shown effectiveness in managing KOA. To address the low adherence rates to physical activity guidelines among KOA patients, the “Move for Knee”™ mobile app was developed. This app offers personalized exercise programs based on user-input data about lifestyle and activity levels, aiming to enhance patient engagement and adherence. Its features include exercise tracking, real-time monitoring, and communication with healthcare providers through an integrated chat function. A randomized controlled trial (RCT) will evaluate the app's efficacy in improving pain, function, and quality of life among individuals aged 45–70 with KOA. The study will compare outcomes from users of the app against a control group receiving standard advice on physical activity. Preliminary expectations suggest that the app will improve adherence to exercise recommendations and overall management of KOA, while also providing cost-effective healthcare solutions. The ultimate goal is to empower patients, enhance their self-management capabilities, and improve their overall health outcomes through an innovative, technology-driven approach. Future research will focus on assessing the app's clinical effectiveness and usability across various patient demographics.